2017
DOI: 10.1111/acer.13499
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Reduces Arterial Remodeling by Inhibiting Sonic Hedgehog‐Stimulated Stem Cell Antigen‐1 Positive Progenitor Stem Cell Expansion

Abstract: Background Cell and molecular mechanisms mediating the cardiovascular effects of alcohol are not fully understood. Our aim was to determine the effect of moderate Ethanol (EtOH) on Sonic Hedgehog (SHh) signaling in regulating possible Sca1+ progenitor stem cell involvement during pathologic arterial remodeling. Methods and Results Partial ligation or sham-operation of the left carotid artery was performed in transgenic Sca1-eGFP mice gavaged with or without ‘daily moderate’ EtOH. The EtOH group had reduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 60 publications
(79 reference statements)
2
26
0
Order By: Relevance
“…Moreover, while we have previously reported that local perivascular knockdown of the Ptch1 receptor attenuates intimal thickening 32 , systemic inhibition of Hh signalling, using a smoothened inhibitor, also significantly decreases arterial Ptch1 and Gli expression concomitant with a reduction in Sca1 + cells and lesion formation in vivo 84 .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Moreover, while we have previously reported that local perivascular knockdown of the Ptch1 receptor attenuates intimal thickening 32 , systemic inhibition of Hh signalling, using a smoothened inhibitor, also significantly decreases arterial Ptch1 and Gli expression concomitant with a reduction in Sca1 + cells and lesion formation in vivo 84 .…”
Section: Discussionmentioning
confidence: 80%
“…were analyzed using SPOT Advanced imaging software. Assuming a circular structure in vivo, the circumference of the lumen was used to calculate the lumen area, the intimal area was defined by the luminal surface and internal elastic lamina (IEL), the medial area was defined by the IEL and external elastic lamina (EEL), and the adventitial area was the area between the EEL and the outer edge, essentially as described by us previously 8,84 .…”
Section: Biochip Preparation and Microfluidic Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Several vascular progenitors have been identified within the vessel wall in both humans and rodents . In particular, the adventitia, which displays increased cell proliferation and inflammation following injury (Seidelmann et al, 2014), contains a heterogeneous population of progenitor/precursor cells with the majority of them expressing Sca1 (Fitzpatrick et al, 2017;Passman et al, 2008;Shikatani et al, 2016;Wan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%